Association Between Triglyceride–Glucose Index and Carotid Plaque Stability in Different Glycemic Status: A Single‐Center Retrospective Study - Guijun Huo; Jin Zheng; Junjie Cao; Lili Zhang; Zhichao Yao; Yuqi Zeng; Yao Tang; Zhanao Liu; Ziyi Tan; Dayong Zhou (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The triglyceride–glucose (TyG) index has been proposed as a reliable marker of insulin resistance. However, its value in patients with carotid plaque stability remains unclear. This study investigated the association between the TyG index and unstable carotid plaque. Methods A total of 12 068 participants were enrolled. Carotid ultrasound was used to determine the stability of carotid plaque. Logistic regression was used to analyze the relationship between the TyG index and unstable carotid plaque. The relationship between the TyG index and unstable carotid plaque was evaluated according to sex, age, and glucose metabolism states. Further, the dose–response relationship between the TyG index and unstable carotid plaque was also determined by restrictive cubic splines. Results Of the 12 068 participants, 11 601 had stable carotid plaque and 467 had unstable carotid plaque. In several different adjustment models, the TyG index is significantly related to the risk of unstable carotid plaque. The association between the TyG index and an unstable carotid plaque was similar between men and women, despite the fact that the odds ratio (OR) tended to be higher in men (OR, 2.80 [95% CI, 2.04–3.83]) than women (OR, 2.07 [95% CI, 1.51–2.82]), and higher in older patients (aged >60 years; (OR, 3.59 [95% CI, 2.74–4.70]) than middle‐aged patients (aged ≤60 years) (OR, 2.00 [95% CI, 1.36–2.95]). The TyG index of patients with different glycemic status was significantly correlated with the risk of unstable carotid plaque, among which the OR value of diabetes (OR, 2.51 [95% CI, 1.87–3.36]) was the highest. The restrictive cubic spline analysis indicated a nonlinear relationship between the TyG index and unstable carotid plaque, with TyG index >8.63 identified as an independent risk factor for unstable carotid plaque. Conclusions The TyG index has a significant association with unstable carotid plaque. The association between the TyG index and unstable carotid plaque is similar between men and women, and the association in older patients is higher than that in middle‐aged patients. In different glycemic status, the association between the TyG index and unstable carotid plaque is highest in patients with diabetes.